Convective and large‐scale mass flux profiles over tropical oceans determined from synergistic analysis of a suite of satellite observations. Issue 13 (12th July 2016) - Masunaga, Hirohiko; Luo, Zhengzhao Johnny
Abstract: A new, satellite‐based methodology is developed to evaluate convective mass flux and large‐scale total mass flux. To derive the convective mass flux, candidate profiles of in‐cloud vertical velocity are first constructed with a simple plume model under the constraint of ambient sounding and then narrowed down to the solution that matches satellite‐derived cloud top buoyancy. Meanwhile, the large‐scale total mass flux is provided separately from satellite soundings by a method developed previously. All satellite snapshots are sorted into a composite time series that delineates the evolution of a vigorous and organized convective system. Principal findings are the following. First, convective mass flux is modulated primarily by convective cloud cover, with the intensity of individual convection being less variable over time. Second, convective mass flux dominates the total mass flux only during the early hours of the convective evolution; as convective system matures, a residual mass flux builds up in the mass flux balance that is reminiscent of stratiform dynamics. The method developed in this study is expected to be of unique utility for future observational diagnosis of tropical convective dynamics and for evaluation of global climate model cumulus parameterizations in a global sense. Key Points: A new strategy is proposed to analyze convective and large‐scale mass fluxes from satellite data The systematic evolution of the mass fluxes is captured in association with convective development The findings have the potential to serve as an observational basis to assess GCM parameterizations